Використання програмного забезпечення для підвищення ефективності моделювання енергетичних мереж - Шевченко, Сергій Юрійович; Данильченко, Дмитро Олексійович (Донецький національний технічний університет, 2022)
Стаття присвячена питанню моделювання елетроенергетичних мереж. В статті розглянуто позитивні та негативні особливості програм для моделювання. Особливу увагу приділено принципам роботи програм. В статті розглянуто такі програми як PSS®SINCAL від компанії Siemens; ETAP від компанії Operation Technology та PowerFactory від компанії DIgSILENT GmbH. В роботі проведено огляд програм та прийнято рішення, що для роботи з моделюванням електричної мережі та впливом компенсуючих пристроїв на електричну мережу найбільш вдалим рішенням буде використання програмного забезпечення PSS®SINCAL від компанії Siemens.

The article is devoted to the topical issue of power grid modeling. The article discusses positive and negative features of simulation programs. Particular attention is paid to the principles of the programs. Such programs as PSS®SINCAL from Siemens; ETAP from Operation Technology and PowerFactory from DIgSILENT GmbH are considered in the article. The PSS®SINCAL software specializes in designing networks from low to ultra-high voltage classes, in symmetrical and non-symmetrical modes of operation, takes into account the installation possibilities of compensating devices and gives recommendations for their installation locations. Basic models enabling mode calculations and shortcircuit calculations as well as simulation of electromagnetic transients are used as the basis of the PSS®SINCAL software. The basic modules include steady state calculations, calculations of short circuit currents, harmonics, system stability and electromagnetic transients. Particular attention is paid to the optimization and planning module, namely reactive power optimization. The module of reactive power optimization in PSS®SINCAL offers methods of optimizing existing equipment by finding the best switching points for reactive power compensation. ETAP software specializes in electrical network and power transmission design. ETAP Grid™ connects network design with detailed substation models, SCADA systems, and real-time transmission network management. This paper covers only 2 modules of ETAP software, namely transmission and distribution modules. PowerFactory captures the full range of functionality from standard features to highly sophisticated and advanced applications, including wind power, distributed generation, real-time modeling, and performance monitoring for testing of surveillance systems. This article reviews only 2 modules of the PowerFactory software, namely the electrical power transmission and distribution modules. The paper reviews the programs and concludes that Siemens' PSS®SINCAL software would be the most successful solution for modeling electric grids and accounting for the effects of compensating devices on voltage levels in electric grids.
Use of software for improving the efficiency of modeling energy networks
Keywords: електрична мережа; енергоефективність; напруга; реактивна енергія; моделювання; програмне забезпечення; PSS®SINCAL; ETAP; PowerFactory; втрати електричної енергії; перетоки реактивної енергії; electric network; energy efficiency; voltage; reactive energy; modeling; software; electric energy losses; reactive energy flows